2022
DOI: 10.3390/ijms23031343
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Functional Profiling of Human Neuropathogenic FOXG1 Alleles in Primary Cultures of Murine Pallial Precursors

Abstract: FOXG1 is an ancient transcription factor gene mastering telencephalic development. A number of distinct structural FOXG1 mutations lead to the “FOXG1 syndrome”, a complex and heterogeneous neuropathological entity, for which no cure is presently available. Reconstruction of primary neurodevelopmental/physiological anomalies evoked by these mutations is an obvious pre-requisite for future, precision therapy of such syndrome. Here, as a proof-of-principle, we functionally scored three FOXG1 neuropathogenic allel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Foxg1 was previously identified as a regulator of sequential neurogenesis in the neocortex via controlling the timing and order of generation of specific neuronal subtypes (26, 29, 30, 40). Foxg1 overexpression in E12 cortical progenitors in vitro was shown to suppress gliogenesis (32, 33). However, in these studies, the Fgf pathway was not identified as a possible FOXG1 target, and Foxg1 knockdown did not result in gliogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Foxg1 was previously identified as a regulator of sequential neurogenesis in the neocortex via controlling the timing and order of generation of specific neuronal subtypes (26, 29, 30, 40). Foxg1 overexpression in E12 cortical progenitors in vitro was shown to suppress gliogenesis (32, 33). However, in these studies, the Fgf pathway was not identified as a possible FOXG1 target, and Foxg1 knockdown did not result in gliogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, in these studies, the Fgf pathway was not identified as a possible FOXG1 target, and Foxg1 knockdown did not result in gliogenesis. Therefore, the endogenous role of FOXG1 could not be established (32, 33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, it promotes morphological maturation of glutamatergic (Brancaccio et al, 2010; Chiola et al, 2019; Yu et al, 2019) and gabaergic (Zhu et al, 2019) telencephalic neurons. Moreover, Foxg1 sustains activity and excitability of these neurons (Frisari et al, 2022; Tigani et al, 2020; Zhu et al, 2019), via an articulated impact on transcription of specific gene-sets (Artimagnella and Mallamaci, 2019; Tigani et al, 2020). Besides, it is in turn transiently promoted by neuronal activity (Fimiani et al, 2016; Tigani et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Foxg1 is an ancient transcription factor mastering a number of developmental processes that take place in the rostral brain. These include early activation of pan- telencephalic (Hanashima et al, 2007), subpallial (Manuel et al, 2010), and paleo-neo- pallial (Muzio and Mallamaci, 2005) programs, promotion of neural precursors selfrenewal (Martynoga et al, 2005), balance between neuronogenesis and gliogenesis (Brancaccio et al, 2010; Falcone et al, 2019; Frisari et al, 2022; Santo et al, 2022), and laminar specification of neocortical neurons (Hanashima et al, 2004; Miyoshi and Fishell, 2012; Toma et al, 2014). Later, it promotes morphological maturation of glutamatergic (Brancaccio et al, 2010; Chiola et al, 2019; Yu et al, 2019) and gabaergic (Zhu et al, 2019) telencephalic neurons.…”
Section: Introductionmentioning
confidence: 99%